2017
DOI: 10.3892/mmr.2017.6699
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis genes in gastric adenocarcinoma identified by cross talk genes in disease-related pathways

Abstract: The aim of the present study was to investigate the prognostic value of genes that participate in the development of gastric adenocarcinoma, via exploring gene cross talk in disease-related pathways. Differentially expressed genes (DEGs) in the gastric samples were identified by analyzing the expression data downloaded from the GEO database. The DEGs were subjected to the human protein-protein interaction (PPI) network to construct the PPI network of DEGs, which was then used for the identification of key gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…Consistent with preceding studies, we demonstrated that ALDH3A1 displayed a high expression level in metastasis colon cancer cells compared with primary colon cancer cells and provided potential biomarkers to develop new therapy to target stem cell caused metastasis [22]. ALDH3A1 was also screened in gastric adenocarcinoma to be used as the prognosis marker [23]. Although ALDH3A1 was screened and presented a predictive role for tumor progression in different cancers, few studies identified this phenomenon.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Consistent with preceding studies, we demonstrated that ALDH3A1 displayed a high expression level in metastasis colon cancer cells compared with primary colon cancer cells and provided potential biomarkers to develop new therapy to target stem cell caused metastasis [22]. ALDH3A1 was also screened in gastric adenocarcinoma to be used as the prognosis marker [23]. Although ALDH3A1 was screened and presented a predictive role for tumor progression in different cancers, few studies identified this phenomenon.…”
Section: Discussionsupporting
confidence: 85%
“…Our study demonstrated that ALDH3A1 in LUAD tumor samples of patients with M1 was significantly upregulated than in patients with M0. Accumulating evidence demonstrated that ALDH3A1 could influence tumor cell proliferation [23][24][25][26]. We, therefore, explored the potential role of ALDH3A1 in mediating cancer cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the drugs are metabolized in the liver by drug-metabolizing enzymes, and the primary drug-metabolizing enzymes are severely dysregulated in HCC, leading to chemotherapy failur e[ 98 ]. Moreover, dysfunction of the drug metabolism-cytochrome P450 pathway (hsa00982) has been reported to induce drug resistance or adverse reactions during chemotherapy in cancer by interrupting drug metabolism and promoting drug excretion [ 99 ]. Arachidonic acid metabolism has been proved to significantly impact the occurrence and development of various malignant diseases [ 100 ].…”
Section: Discussionmentioning
confidence: 99%
“…The expression levels of ALDH3A1 in surgically resected cancer tissues correlate with the prognosis of patients with gastric cancer. Combined with other differentially expressed genes, ALDH3A1 shows diagnostic efficacy in patients with gastric cancer (Zhao et al, 2017). The impact of ALDH3A1 expression status on the prognosis of pancreatic cancers needs further validation in relationship with therapeutic intervention such as adjuvant chemotherapy.…”
Section: Discussionmentioning
confidence: 99%